Determinants of dietary diversity among pregnant women in Laikipia County, Kenya: a cross-sectional study. Issue 1 (December 2017) - Kiboi, Willy; Kimiywe, Judith; Chege, Peter
Abstract Background Dietary diversity has continued to gain widespread attention among the population since it has evidently been associated with nutrient adequacy. A diverse diet has been shown to reflect nutrient adequacy since no one food can meet the nutritional requirement of a person. Pregnant women have been considered vulnerable to malnutrition due to their increased nutrient requirement and therefore a variety of foods in their diet is considered imperative in ensuring adequate nutrient intake. To promote dietary diversity, it is important to understand the factors associated with it. This paper therefore assessed the determinants of dietary diversity among pregnant women in Laikipia County, Kenya. Methods The study was a cross-sectional analytical study consisting of 254 pregnant women attending antenatal clinic at Nanyuki Teaching and Referral Hospital in Laikipia County, Kenya. Results The mean Dietary Diversity Score (DDS) was 6.84 ± 1.46 Standard Deviation (SD), with cereals being the most (99%) commonly consumed food group. Adjusted Logistic Regression (AOR) analyses revealed education level (AOR = 2.78; (95% Confidence Interval (CI) 1.06, 5.32;p  < 0.001), employment status (AOR = 2.29; CI 1.18, 4.14;p  = 0.003), monthly income (AOR = 2.08; CI 1.32, 3.03;p  < 0.001), household assets (AOR = 1.93; CI 0.73, 6.90;p  = 0.030), land ownership (AOR = 0.64; CI 0.44, 2.25;p  = 0.040), and morbidity (AOR = 0.78; CI 0.36, 2.34;p  = 0.010) among the pregnant women as the variables that influenced their dietary diversity. Conclusion Socioeconomic factors (education level, employment status, monthly income, household assets and land ownership) have been shown to influence dietary diversity in this study. New policies and intervention programmes targeting these determinants of dietary diversity should therefore be enacted, while the existing ones should be supported and monitored particularly among the vulnerable populations. Such policies and programmes among pregnant women will ensure improved dietary diversity and adequate nutrient intake. Similarly, since morbidity incidence among pregnant women have been shown to significantly influence dietary diversity, public health awareness campaign on the importance of early detection and timely treatment of diseases among pregnant women should be launched by the relevant stakeholders.